2020
DOI: 10.3390/app10031024
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Imaging of Tattoo Inks: Phantom and Clinical Evaluation

Abstract: Photoacoustic imaging (PAI) is a novel hybrid imaging modality that provides excellent optical contrast with the spatial resolution of ultrasound in vivo. The method is widely being investigated in the clinical setting for diagnostic applications in dermatology. In this report, we illustrate the utility of PAI as a non-invasive tool for imaging tattoos. Ten different samples of commercially available tattoo inks were examined for their optoacoustic properties in vitro. In vivo PAI of an intradermal tattoo on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, these results may be biased because picosecond sources are often used for harder-to-treat tattoos, such as professional tattoos with mixed colors. Photoacoustic imaging may be useful as a clinical adjunct for the objective preoperative evaluation of tattoos and potentially as a guide/monitor for laser-based tattoo removal procedures [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, these results may be biased because picosecond sources are often used for harder-to-treat tattoos, such as professional tattoos with mixed colors. Photoacoustic imaging may be useful as a clinical adjunct for the objective preoperative evaluation of tattoos and potentially as a guide/monitor for laser-based tattoo removal procedures [31].…”
Section: Discussionmentioning
confidence: 99%
“…There are emerging dermatological applications which can benefit from PAI. For example, Bolookat et al demonstrated that tattoo inks are PA active and the delineation of the shape of an in vivo intradermal tattoo can be visualized by PAI [55]. PAI can potentially be exploited in the preoperative evaluation of tattoos before its laser removal process and in guiding the removal process by objectively visualizing remaining tattoo inks in the dermal region.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In this paper, an introductory tattoo study was conducted on synthetic tattoos made on 2L tissue‐like PDMS phantoms. Tattoo ink absorbs the light and reflects the light [13], while DR measures the re‐emitted light. From this re‐emittance, we calculated the absorption coefficients of the 2L phantom based on the Cp.…”
Section: Introductionmentioning
confidence: 99%
“…Several imaging techniques, such as two‐photon microscopy [11], X‐ray computed tomography [12], photoacoustic imaging (PAI) [13], optical coherence tomography (OCT) [14], and Raman microscopy [15] are excellent for determining the chemical composition of tattoo ink. However, these methods are limited in penetration depth, because tattoo ink is mainly present in the dermal layer (~2.0 to 4 mm) of the skin [16].…”
Section: Introductionmentioning
confidence: 99%